Legal Protection for Local Animators in Animation Production in the Digital Era - Aldo Sariski (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
Digital transformation has opened up great opportunities for the creative industry, but at the same time presents complex challenges for the legal protection of local animators. This research aims to analyze the forms of legal protection for local animators in the digital era and identify obstacles in its implementation. The research method used is normative juridical with a statutory approach. The research results show that legal protection for animators has been accommodated through Law Number 28 of 2014 concerning Copyright as cinematographic works which include moral rights and economic rights, implemented through license agreements. However, implementation is still hampered by high rates of digital piracy, the weak bargaining position of animators in work contracts (work for hire), and the uncertainty of freelance work status. Synchronization between copyright regulations and labor law is needed to ensure the welfare of local animators in Indonesia.